Determinan Nilai Perusahaan Sektor Property yang Terdaftar di BEI Periode 2019-2021 - Musthofa, Rizal Hanif; Chomsatu, Yuli (Fakultas Ekonomi dan Bisnis dan LPPM Universitas Negeri Jakarta, 2022)
The motive of this research is to take a look at how the impact of debt policy, capital structure and company size on firm fee. The topics for the studies here are assets/actual property companies indexed on the Indonesia inventory exchange or BEI for the duration 2019-2021, samples were taken through a technique known as purposive sampling, 17 organizations had been acquired with the standards met. Researchers used secondary data from financial statements. And for the method in reading the researcher the use of more than one linear regression. And the outcomes of this look at suggest that: 1) debt policy has an effect on firm fee, 2) capital structure has an impact on company, 3) however, firm size has no impact on company cost.